Association of National Eye Institute Visual Function Questionnaire 39 Scores With Visual Function in Age-related Macular Degeneration Over 24 Months - Yao, Catherine S; Lue, Victoria; Stinnett, Sandra S.; Luhmann, Ulrich F.O.; Lad, Eleonora M. (Ophthalmic surgery, lasers & imaging, 2025)
Background and Objective The aim of this study was to determine the National Eye Institute Visual Function Questionnaire 39 (NEI-VFQ39) score association with visual function (VF) tests in early (eAMD) and intermediate (iAMD) age-related macular degeneration. Patients and Methods Thirty-three eAMD, 47 iAMD, 21 control subjects completed the NEIVFQ39 at baseline and 22 eAMD, 31 iAMD, 17 control subjects at 24 months. Best-corrected visual acuity (BCVA), low luminance visual acuity (LLVA), cone contrast test (CCT), microperimetry (MP) with eye-tracking (MAIA), and dark adaptation (DA) testing were administered during both visits. Results At baseline and 24 months, iAMD patients scored lower NEI-VFQ39 composite scores than eAMD participants and controls (P < 0.05); longitudinal changes showed no differences between groups. Baseline composite scores were associated with LLVA (Spearman-r = 0.33, P < 0.001), percent-reduced threshold (PRT) (r = −0.33, P = 0.001), and absolute threshold (AT) (r = 0.31, P = 0.003) on MP. Conclusion Although the NEI-VFQ39 did not detect change over 24 months, these results support the use of NEI-VFQ39 as a cross-sectional tool in iAMD.